AN ANALYSIS OF FIGURATIVE LANGUAGE IN NICOLE’S ALBUM BY NIKI - Nenni Triana Sinaga; Angelica Septina Ambarita; Rina O. Simarmata (J-Shelves of Indragiri (JSI), 2024)
This research aims to determine the type of figurative language in Niki's song lyrics on Nicole's album and the type of figurative language that is most dominant in Niki's song lyrics on Nicole's album. This research has two problems, namely the first is looking for figurative language in Niki's album and looking for the most dominant figurative language in Niki's album. The method used is the Qualitative Descriptive Method. The data for this research are song lyrics that contain figurative language. The data source for this research is Nicole Albums which was released on August 11, 2022. This research data is the song lyrics of five songs taken randomly by Niki, namely "Backburner", "Anaheim", "Oceans & Engines", On "Home Drive" and "Take a Chance With Me". The instruments of this research are observation and documentation. The results obtained were 8 types of Figurative Language, namely 5 Alliterations, 10 Hyperbole, 14 Metaphors, 3 Similes, 4 Symbols, 3 Personifications, 1 Metonymy, 6 Irony. And the most dominant figurative language used in Nicole's albums is metaphor, with the percentage of alliteration accounting for 11%, hyperbole 22%, metaphor 30%, simile 7%, symbol 9%, personification 7%, metonymy 2%, and finally 13% irony.